1993
DOI: 10.5254/1.3538303
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic Addition of Brominated Poly(Isobutylene-co-4-Methylstyrene) to Olefins Catalyzed by Zinc Salts: A Model Study

Abstract: The chemical reactivity of a new elastomer based on brominated poly(isobutylene-co-4-methylstyrene) in electrophilic additions to olefins has been investigated using model compounds as well as appropriate polymers. The reactions catalyzed by zinc salts are influenced by the solubility as well as the composition of the catalyst. While the reactivity of zinc bromide is limited by its low solubility in nonpolar medium, zinc oxide and zinc stearate can afford excellent results once an induction period has elapsed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…It is not clear why considerable spread of the data occurs in Figure 9. Overall, the above adhesion results are consistent with the work of Frěchet et al 8 At low bonding temperatures, reaction of the BrPMS groups in BIMS to the double bonds in BR is more favorable, resulting in interfacial cocure. At high bonding temperatures, reaction of the BrPMS groups in BIMS to the BrPMS groups in the same polymer is more favorable.…”
Section: CMsupporting
confidence: 82%
See 1 more Smart Citation
“…It is not clear why considerable spread of the data occurs in Figure 9. Overall, the above adhesion results are consistent with the work of Frěchet et al 8 At low bonding temperatures, reaction of the BrPMS groups in BIMS to the double bonds in BR is more favorable, resulting in interfacial cocure. At high bonding temperatures, reaction of the BrPMS groups in BIMS to the BrPMS groups in the same polymer is more favorable.…”
Section: CMsupporting
confidence: 82%
“…Interfacial cocure can also occur by direct chemical bonding if the two polymers carry functional groups reactive to each other, such as the cocuring between terpolymer of isobutylene, pbromomethylstyrene, and p-methylstyrene (BIMS) and nylon 6,7 or between BIMS and IR or BR, studied in this work. The chemical reactivity of BIMS by electrophilic additions to olefins, depicted briefly in Figure 1, was investigated by Frěchet et al 8 by using model compounds as well as appropriate polymers. The mechanism of the addition process involves the initial formation of carbocationic complexes with zinc salts, followed by addition to the double bonds of the olefins.…”
Section: Introductionmentioning
confidence: 99%
“…Because a halogenated SEBS offers advantages of having an elevated upper service temperature, better flame retardancy, and an increased polarity providing better adhesion properties, our interest in the chemical modification of SEBS has led us to study the possibility of incorporating bromine into such copolymers. Furthermore, recent studies of brominated poly(p-methylstyrene-co-isobutylene) have shown that a brominated methyl group of a pmethylstyrene unit affords opportunities such as crosslinking through an electrophilic addition to olefins, 1 and incorporating novel properties through nucleophilic substitution of the bromine. 2,3 Thereby, our bromination study was conducted on a specifically made modified SEBS block copolymer, i.e., a poly(p-methylstyrene-costyrene)-block-poly(ethylene-co-butene)-blockpoly(p-methyl styrene-co-styrene) (pMSS-EBpMSS).…”
Section: Introductionmentioning
confidence: 99%
“…We now turn to a more quantitative analysis of the bromination kinetics. In the past, several research groups studied the bromination of styrene (or styrene-like monomers) as well as polystyrene under various conditions. , ,− For instance, Robertson et al reported that the bromination of mesitylene in acetic acid follows a second-order kinetics at low bromine concentrations (10 −2 −10 −3 M). Andrews , and Wright groups argued that bromination substitution follows a combined first-order (in bromine) and second-order (in bromine) reaction kinetics. R = d [ Br 2 ] d t = k 1 [ ArH ] [ Br 2 ] + k 2 [ ArH ] [ Br 2 ] 2 …”
Section: Resultsmentioning
confidence: 99%
“…Diverse catalysts, including AlCl 3 , FeCl 3 , SnCl 4 , SbCl 5 , TiCl 4 , ZnO, ZnCl 2 , and ZnBr 2 , have been reported to increase the rate of PS bromination leading to PBr x S. While catalyzed bromination typically results in relatively high reaction rates, nonrecyclable catalyst waste and the purification of catalyst represent certain drawbacks for such reactions. In their original papers, Kambour and co-workers showed that in the absence of light solvents with a moderate dipole moment, i.e., chloroform or nitrobenzene, are capable of polarizing the Br 2 molecule, thus enabling electrophilic substitution addition of bromine in the para position of the phenyl ring of PS without using a catalyst. , While the reaction rates have been considerably slower than those reported for catalyzed brominations, the absence of catalysts and thus ease of purification are great benefits of such “solvent-catalyzed” bromination reactions.…”
Section: Introductionmentioning
confidence: 99%